The Effect of Differences in Growing Altitude on the Total Flavonoid Content Single Clove Garlic (Allium sativum Linn) - Styawan, Anita Agustina; Putra, Rayhantana Rizky (Journal of Food and Pharmaceutical Sciences, 2026)
Single garlic belongs to the Amaryllidaceae family and contains flavonoid compounds with antioxidant activity. However, the use of herbal ingredients often shows inconsistent effects because differences in growing locations, such as soil and climate conditions, can influence the amount of flavonoids produced. The purpose of this study was to determine the difference in total flavonoid content of single garlic (Allium sativum Linn) based on the influence of growing locations in Boyolali Regency and Karanganyar Regency. This study used 2 kg of single garlic (Allium sativum Linn) samples, which were then extracted using the maceration method with 96% ethanol solvent. The total flavonoid content was determined using the UV-Vis spectrophotometry method. The results showed that the quantitative test using UV-Vis spectrophotometry obtained a maximum wavelength of 426 nm with a curve equation of y=0.0151x – 0.0033. The average total flavonoid content from Boyolali Regency was 0.5867 mgQE/g and from Karanganyar Regency was 0.5867 mgQE/g and 0.1495 mgQE/g. Based on statistical test data, it was found that the significance value was 0.002, where the result had a P<0.05 value, which means that there was a significant difference in total flavonoid content based on the growing location.